Monocentric Concepts in Phonetic Errors of ‘Bimanese’ EFL Learners - Irianti, Irianti (English Literature Study Program, 2023)
The open debate between monocentric and plurecentric concepts on pronunciation makes this research carried out. Monocentric is the concept which tends to emphasize an English learning approach for non-native speakers based on standard English or anglo-american style and believes in the existence of error sounds, while plurecentric considers the errorneous as the variety of English instead of error sounds. However, the researcher only tried to investigate the error, which sounded particularly phonetic, by taking 10 Bimanese college students. 50 words were given to the participants, and the record test was used during the pronunciation test. This test became the data to answer what phonetic errors were produced by Bimanese EFL learners using error analysis in the form of qualitative method and descriptive analysis. The communication problems that were caused by phonetic errors were identified as well becoming the second research question to be answered. This was done considering the relationship between intelligibility and pronunciation. The communication processes of two Bimanese Youtubers with foreigners were investigated for understanding the phenomenon of intelligibility and pronunciation using observation tests on four video vlogs. The findings showed that vowels were the most deviated errors produced by Bimanese. The deviation that occurred was barely caused by fossilization and mother tongue interference; the illiteracy of the participants in the pronunciation and the inconsistency of English sound systems took the most. Eventually, the researcher discovered misunderstandings and a lack of confidence that were caused by phonetic errors in the communication process.